Identifying and assessing factors in community participation for effective sustainable urban renewal the case of Estero de Paco - Arevalo, Albrecht Arthur N. (School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
This study examines community participation in the urban renewal of Estero de Paco in Manila City, the flagship project in the ongoing renewal of the Pasig River's tributaries or esteros. With the ultimate goal of restoring the river's environs and improving its water quality, the project focuses on uplifting the conditions of informal settlers living along the estero through community rehabilitation and construction of infrastructure. Qualitative data obtained from document reviews, and interviews and focus group discussion with several major stakeholders, and quantitative data from the use of survey questionnaires shed light on the factors that affect participation among community members, the types of participation present, and the project's overall effectiveness and sustainability. The study concludes that participation among community members is mainly hindered by practical (e.g. money, time) and personal (e.g. feelings of discomfort) factors, but strong local governance at the barangay level has been proven as effective in overcoming these to a certain. Using Pretty's (1995) Typology of Participation, it has been found that there are several types of participation present in Estero de Paco, with the highest being self-mobilization through the actions of the community-based River Warrior people's organization, a reflection of the community's ownership of the project and its initiative to self-organize. Lastly, an examination of the project's effectiveness and sustainability reveal shortcomings in economic and social sustainability aspects of the project, highlighted by problems encountered during the resettlement process, which is inextricably tied with its success as an urban renewal project. As these are still unaddressed and could have the capacity to grow even more alarmingly in the near future, it is difficult to label the Estero de Paco project as sustainable. This study recommends the consideration of several factors in designing community participation programs, a higher degree of involvement of resettles in the planning of resettlement locations, and the strengthening of coordination among local government units for more effective implementation of plans and policies.